ANCAMAN ERUPSI KAWAH IJEN TERHADAP MASYARAKAT LERENG IJEN (KABUPATEN BONDOWOSO) - Dhimas Bagus Virgiawan (ASANKA : Journal of Social Science and Education, 2020)
Ijen caldera complex is a volcano that has a 7 km diameter elliptical caldera which only leaving a northern caldera wall curving towards the southward. Ijen crater as a youngest volcano and still active today stratigraphically composed of lava flow, pyroclastic flow sediments, and pyroclastic fallout. Threats that arise if an eruption occur is pyroclastic flow, pyroclastic fallout, lava flow, lahar flow, and water of ijen crater. The existance of vulcanic activity of Ijen crater impact positively to the society which live around the Ijen mountain region. Their economy rest on sulphur mining and the soil fertility which is used to potato, cabbage and coffee crop cultivation. If this happen it could be a serious threat for the environment, include the population settled around volcano and along the river upstream in the lake of this crater and is a catastrophe. The disaster can be huge because water volume of large enough crater lake and very acidic, besides the result of explotion such as hot clouds, phreatic eruption in the form of lava eruption is also possible to happen.